Disrupting Ageism in “Active for Life” Research & Recreational Pursuits: A Professor’s Lived Experience of Leading and Following - Lloyd, Rebecca (Université d'Ottawa | University of Ottawa, 2026)
This motion-sensing inquiry into ageist attitudes and beliefs in competitive partnered dance and active aging research offers new insight into to the phenomenon of being “active for life”. The dual positionality of the researcher as being both an emerging leader in active aging research and a follower in salsa dance adds a unique, embodied perspective to leadership scholarship. Her approach is vulnerable as she reveals her own ageist assumptions when studying physical activity in senior living communities. She also reflects upon the ways she experiences ageism in her recreational partnered dance pursuits. The aim in sharing lived experiences through first-person perspectivity is to inspire age-friendly practices in higher education and more positive perspectives about getting older – that optimal challenge, creative engagement, and joy may be inherent in active for life pursuits at any age.
Keywords: Ageism; Physical literacy; Active aging; Active for life; Phenomenology